Air vs. Road Decision for Endovascular Clot Retrieval in a Rural Telestroke Network - Gangadharan, Shyam; Lillicrap, Thomas; Miteff, Ferdinand; Garcia-Bermejo, Pablo; Wellings, Thomas; O'Brien, Billy; Evans, James; Alanati, Khaled; Levi, Christopher; Parsons, Mark W.; Bivard, Andrew; Garcia-Esperon, Carlos; et al. (Frontiers in Neurology, 2020)
Background and Purpose Telestroke aims to increase access to Endovascular Clot Retrieval (ECR) for rural areas. There is limited information on transfer workflow for ECR in rural settings. We sought to describe the transfer metrics for ECR in a rural telestroke network with respect to decision making. Methods Retrospective cohort study on consecutive patients transferred to the comprehensive stroke center (CSC) for ECR in a rural hub-and-spoke telestroke network between April 2013 and October 2019, by road or air. Key time-based metrics were analyzed. Results Sixty-two patients were included. Mean age was 66 years (standard deviation [SD], 14) and median National Institutes of Health Stroke Scale 13 (interquartile range [IQR], 8-18). Median rural-hospital-door-to-CSC-door (D2D) was 308 minutes (IQR, 254-351), of which 68% was spent at rural hospitals (door-in-door-out [DIDO]; 214 minutes; IQR, 171-247). DIDO was longer for air transfers than road (P=0.004), primarily because of a median 87 minute greater decision-to-departure time (Decision-DO, P<0.001). In multiple linear regression analysis, intubation but not thrombolysis was associated with significantly longer DIDO. The distance at which the extra speed of an aircraft made up for the delays involved in booking an aircraft was 299 km from the CSC. Conclusions DIDO is longer for air retrievals compared with road. Decision-DO represents the most important component of DIDO, being longer for air transfers. Systems for rapid transportation of rural ECR candidates need optimization for best patient outcomes, with decision support seen as a potential tool to achieve this.